Estate planning - Simon, Jordan S.; Mashinski, Joseph (--For dummies., 2023)
"Estate Planning For Dummies teaches you the ins and outs of estate planning. This everyone-friendly guide walks you through building a solid estate plan, whatever your current financial situation. In easy-to-understand language, you'll learn the ins and outs of estate planning, including what happens to your stuff--cash, real estate, businesses, retirement funds, everything--when you pass away. This new edition is updated for the many recent changes in estate taxes and inheritance law"--